2015
DOI: 10.1038/sc.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Access to surgical upper extremity care for people with tetraplegia: an international perspective

Abstract: Study design: Survey. Objectives: To determine whether upper extremity reconstruction in patients with tetraplegia is underutilized internationally and, if so, what are the barriers to care. Setting: International-attendees of a meeting in Paris, France. Methods: One hundred and seventy attendees at the Tetrahand meeting in Paris in 2010 were sent a 13-question survey to determine the access and utilization of upper limb reconstruction in tetraplegic patients in their practice. Results: Respondents ranged the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Of the 27 recommendations made for specialties and specialists offering nerve transfer, only two posts in our study recommended a plastic surgeon, despite plastic surgeons being on the forefront of nerve transfer surgery and peripheral nerve research. 7,13 Similar biases can be introduced in the discussion of medical centers. In response to a post about a speci c center performing nerve transfer, one commenter made plans to travel out-of-state to receive a consult, believing this was a unique opportunity unavailable elsewhere.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of the 27 recommendations made for specialties and specialists offering nerve transfer, only two posts in our study recommended a plastic surgeon, despite plastic surgeons being on the forefront of nerve transfer surgery and peripheral nerve research. 7,13 Similar biases can be introduced in the discussion of medical centers. In response to a post about a speci c center performing nerve transfer, one commenter made plans to travel out-of-state to receive a consult, believing this was a unique opportunity unavailable elsewhere.…”
Section: Discussionmentioning
confidence: 91%
“…[7][8][9][10] Although studies have shown signi cant gains in upper extremity range of motion and strength after nerve transfer 11,12 , use of upper extremity reconstruction remains low around the world. 13,14 One barrier which may contribute to low utilization rates is lack of awareness in the SCI community of surgical options to improve upper extremity function. 15 To address this lack of knowledge, it is important to identify where individuals seek information on treatment options, and what information is available.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported an underutilization of surgeries to restore upper limb function in tetraplegia. 17,18 That is, individuals who are candidates to receive surgery do not undergo the procedure. Two articles in the supplement direct attention to eliminating unnecessary barriers in the delivery of care and empowering patients to make informed choices.…”
Section: Making the Choice For Surgerymentioning
confidence: 99%
“…Improving upper extremity (UE) function is a high priority for people living with cervical spinal cord injury (SCI). [1][2][3][4][5] Improved UE function increases independence 6,7 and may reduce health care costs. Surgical interventions such as UE nerve [8][9][10][11][12][13][14] and tendon transfers 15 may supplement comprehensive rehabilitation and provide a path toward the return of UE function.…”
Section: Introductionmentioning
confidence: 99%
“…In the SCI community, there is limited awareness that UE surgery is an option to enhance hand function. 3,17 Others may have difficulty finding and understanding inaccessible and complex health information, physically accessing resources, 17 navigating health care systems, 4 or are not referred to UE surgeons. 3 The variable surgical outcomes after UE surgery in SCI 10,12,18 may have resulted in low adoption of nerve and tendon transfer surgeries; however, recent work supports their benefit.…”
Section: Introductionmentioning
confidence: 99%